2017
DOI: 10.1007/s12613-017-1424-3
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive behavior and processing maps of low-expansion GH909 superalloy

Abstract: The hot deformation behavior of GH909 superalloy has been studied systematically using isothermal hot compression tests in temperature range of 960-1040°C at strain rates of 0.02-10 s −1 with height reduction up to 70%. The relations considering flow stress, temperature, and strain rate have been evaluated via power-law, hyperbolic sine, and exponential constitutive equations in different strains conditions, and exponential equation is first found more appropriate for process modeling. The processing maps for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Lypchanskyi et al [41] identified the undesirable and potentially favorable thermal deformation parameters of Nickel-Based Superalloy. Yao et al [42] created the processing maps of the GH909 superalloy. Chen et al [43] constructed a processing map of GH4698 alloy at high-temperature deformation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lypchanskyi et al [41] identified the undesirable and potentially favorable thermal deformation parameters of Nickel-Based Superalloy. Yao et al [42] created the processing maps of the GH909 superalloy. Chen et al [43] constructed a processing map of GH4698 alloy at high-temperature deformation conditions.…”
Section: Introductionmentioning
confidence: 99%